“Social Elevator”: Research of Affirmative Action Program - E. A. Tarasova (Высшее образование в России)
This work investigates the academic performance of students enrolled in the “Social Elevator” program at Higher School of Economics (HSE University), which operates under the principle of affirmative action and aims to assist those students who have lower chances of admission due to various social reasons in a highly competitive environment. Objective admissions in Russian universities and the high selectivity of the HSE University, discussed in this paper, do not confidently allow the application of conclusions from foreign studies to the Russian experience. The program had not been previously researched. It was assumed that students of the program would show higher performance than their peers admitted on a general basis – this assumption follows from qualitative research that found that students of this program possess a progressive narrative of overcoming inequality. Regression with dummy variables based on administrative data on student performance and survey data on the socio-economic status of students are used for the analysis. According to the regression analysis results, all else being equal, students of the “Social Elevator” program demonstrate lower performance than students admitted on budgetary places on general grounds, although they average grades at the “good” level and therefore have a chance to get a return to education and overcome inequality. Further research on the topic is required to separate the secondary effects of inequality, as well as to assess the actual social mobility of students participating in the program. The results can be useful in designing educational policy in the field of expanding access to higher education.